PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KEMAMPUAN NUMERASI MATEMATIKA - Sri Wiyata; Sri Suwartini (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The purpose of this study was to describe the effect of the guided inquiry learning model on mathematical numeracy skills in MTs students on social arithmetic material. This research is a quasi-experimental research (Quasi Experiment). The subjects of this study were all seventh grade students whose school implemented the 2013 curriculum and graded grade increase exam scores above 70. The population in this study were all seventh grade students of MTs Negeri Gantiwarno as many as 147 people. The sample in this study was determined by using a random sampling technique. The sample in this study were 28 people. The sample of this study were students of MTs Negeri Gantiwarno, Klaten. The instrument used in this study was a test of mathematical numeracy skills in social arithmetic. The inquiry learning approach is measured by the achievement of student learning outcomes using tests of cognitive abilities achieved by students that have been validated and reliable. The data analysis technique used was the ANOVA test, then continued with the Independent Sample t Test. The results showed that the guided inquiry learning model influenced mathematical numeracy by 77.7% and another 22.3% was influenced by other aspects.